Social sustainability of information and communication technology (ICT) telecentres in rural communities in Malaysia - Badsar, Mohammad; Abu Samah, Bahaman; Abu Hassan, Musa; Osman, Nizam; Mohd Shaffri, Hayrol Azril (American-Eurasian Network for Scientific Information, 2011)
The main purpose of this paper was to determine factors that influence social sustainability of Information and Communication Technology (ICT) telecentres in rural communities in Malaysia. A cross sectional survey method was employed in the study. Data were collected from 360 respondents who were randomly selected from users of the PID and MID telecentres and analyzed using AMOS and SPSS software. Results of the Structural Equation Modeling (SEM) analyses show that the information characteristic variable had better contribution than individual and telecentre characteristics to predict the social sustainability of ICT project. The findings of this study provide practical implication and lesson for governments and donor agencies involved with telecentres development.